Between Efficiency and Participation: A Democratic Review of Village Head Candidacy Limits in Bangkalan Regency - Agus Supriyo; Samsul Arifin; Achmad Hariri; Asis Asis (Journal of Judicial Review, 2025)
The regulation of village head elections in Indonesia reflects the state’s effort to balance democratic participation with administrative efficiency at the local level. However, a legal gap arises when restrictions on the number of village head candidates are implemented through derivative regional regulations, raising questions about their compatibility with democratic principles and the constitutional guarantee of political rights. This study aims to examine whether the limitation of village head candidates in Bangkalan Regency is consistent with the concept of democracy and to assess the implications of the additional selection mechanism based on a scoring system. This research employs a normative legal research method using a statute approach and a conceptual approach by analyzing constitutional provisions, statutory regulations, ministerial regulations, and regent regulations related to village head elections. The findings reveal that the restriction of candidates is legally valid from an administrative perspective, as it is justified by considerations of effectiveness, efficiency, budgetary limitations, and the need to prevent social conflict in simultaneous village head elections. Nevertheless, from a democratic perspective, such restrictions present a normative dilemma, as they have the potential to reduce the quality of political participation and undermine the principle of political equality, particularly for prospective candidates who lack access to adequate information or resources. The use of a scoring system in additional selection further intensifies this issue by introducing subjective and uneven assessment criteria that may disadvantage certain segments of society. This study contributes to legal scholarship by demonstrating that while administrative efficiency is an important objective, it should not override fundamental democratic values. The research underscores the need for transparent, accountable, and participatory regulatory designs to ensure that local election governance upholds both administrative effectiveness and the protection of citizens’ civil and political rights within Indonesia’s democratic framework.